Evidence of functional connectivity disruptions between auditory and non-auditory regions in adolescents living with HIV - Madzime, Joanah; Jankiewicz, Marcin; Meintjes, Ernesta M.; Torre, Peter; Laughton, Barbara; Holmes, Martha J. (Frontiers in Systems Neuroscience, 2025)
IntroductionChildren living with perinatally acquired HIV (CPHIV) demonstrate hearing impairments and language processing delays even in the presence of combination antiretroviral therapy (cART). Investigations on the effect of HIV on the auditory system have predominantly focused on the peripheral auditory system. Additionally, language processing requires the efficient interaction between central auditory system (CAS) brain regions and non-auditory regions. Investigating the functional connectivity (FC) within the CAS and between the CAS and non-auditory regions may reveal the influence of HIV on regions involved in auditory function.MethodsWithin a Bayesian statistical framework, we used resting-state functional magnetic resonance imaging to map FC in the CAS as well as between CAS regions and non-auditory regions of 11-year-old CPHIV. Graph theory was used to investigate the regional effects of HIV on brain network properties. We explored the relationships between FC and neurocognitive outcomes. We hypothesized that CPHIV would show disruptions in FC between CAS regions as well as between CAS and non-auditory regions. Secondly, we hypothesized that in CPHIV, regional brain network properties would be altered compared to their uninfected peers (CHUU). Finally we hypothesized that FC and functional network regional outcomes would be related to neurocognitive outcomes.ResultsOur investigation revealed lower FC of the primary auditory cortex (PAC) in CPHIV as well as disruptions in FC between CAS regions and non-auditory regions including hippocampal sub-regions, the lingual gyri and basal ganglia. Functional network analysis revealed lower nodal degree and efficiency in CAS regions including the cochlear nucleus/superior olivary complex and the inferior colliculus. We also report associations between the nodal efficiency of middle temporal and superior frontal regions and delayed recall, a neurocognitive marker of working memory, present in CHUU but not in CPHIV.DiscussionOur results demonstrate FC alterations in the PAC and between CAS regions and non-auditory regions involved in limbic, visual and motor processing, as well as disruptions to the regional properties of the CAS regions in the functional brain network. These results provide insight into the state of the CAS FC in the presence of HIV and its possible role in the hearing and language impairments seen in this population.